ASSESSMENT OF ECONOMIC OF POTATO FARMER OF KANPUR DISTRICT (UTTER PRADESH) (International Journal of Food and Nutritional Sciences, 2022)
An examination of constraints in context to production and marketing of potato crop shows that the poor quality seed inadequate and imbalanced use of fertilizer, plant protection measures, irregular supply of electricity for tube wells and unawareness about the modern cultural practices were highly responsible for lower return to the potato growers, there is need to overcome these constraints. There is need to use good quality of seeds of potato varieties, which are resistance of insect pest and diseases and maturity at different intervals. The potato growers should be advised to used recommended package of practices, particularly use of fertilizers, irrigation and plant protection measures for obtaining higher yield and income from potato crop. There is also need to provide cold storage facilities to avoid forced sales, provide higher price of produce and make available the potato throughout the year.